A systematic review assessing the osseoincorporation potential of trabecular dental implants: A current evidence and future directions - Karuna S. Patwardhan; Nisha Puranik; Hema Kanathila; Santosh Yamanappa Nelogi; Vasanti P Jirge (The Journal of Indian Prosthodontic Society)
Statement of Problem: There is lack of evidence of studies conducted to compare the integration of soft and hard tissues of conventional implants and porous tantalum trabecular metal (PTTM dental implants). Purpose: This systematic review assessed the clinical outcomes evaluating the hard and soft-tissue parameters for PTTM dental implants when compared with conventional titanium dental implants. Materials and Methods: The Preferred Reporting Items for Systematic review based on PRISMA 2020 checklist was used as guideline for reporting this protocol. The search was conducted in SCOPUS, PUBMED, Cochrane library, and EMBASE databases for the studies published from January 1, 2010, to January 1, 2023. The chosen publications’ cross-references were further examined, and studies whose whole texts were not available through the computerized search were manually looked up. Results: Through search strategy a total of 1152 articles were yielded. After screening titles and abstracts, 9 articles were further screened for full text. After critical analysis, according to the eligibility criteria of this review, 7 articles were included in this systematic review for data extraction. Four studies revealed mean of 98.8% survival rate for trabecular implants. Histologically, 2 studies showed upregulation of bone morphogenic proteins, collagens, and growth factors with respect to trabecular dental implants. Conclusion: From this study, it can be concluded that PTTM dental implants showed a better osseoincorporation potential than titanium implants. However, a longer follow-up period is required to assess its true potential.